Aflatoxin (M1 and B1) Contamination of Locally Repacked Milk Powder in South-Western Nigeria - Oyeyipo, O.O., ⃰ Oyeyipo, F.M. and Ayah, I.R. (Sokoto Journal of Medical Laboratory Science)
Aflatoxins are toxic fungal metabolites found in foods and feeds. When mammals eat aflatoxin B1 (AFB1)-contaminated foods/feeds, they metabolize the toxin and excrete aflatoxin M1 (AFM1) in milk. This paper reports the levels of aflatoxins M1 (AFM1) and B1 (AFB1) contamination in one hundred and twenty- five locally repacked powdered milk samples from five States in the South-Western region of Nigeria. Repacked milk samples in polyethylene bags (nylons) and plastic containers were purchased and assessed for fungal contaminants. Samples were analyzed for AFM1 using a rapid diagnostic kit (Aflasensor), Immunoaffinity Column (IAC) and High-Performance Liquid Chromatography (HPLC) with fluorescence detection, for comparison. AFB1 was screened using IAC/HPLC. Aspergillus, Fusarium, Penicillium, Rhizopus and Mucor species were the predominant fungal isolates. AFM1 was detected in 41(32.8%) and 67 (53.6%) samples by the Aflasensor kit and IAC/HPLC, respectively, at levels ranging from 0.02 - 0.46 µg/kg. AFB1 was found in 119 (95.2%) samples analyzed at concentrations of 29.7-79.4 µg/kg. Whereas the AFM1 found in the repacked milk powder samples were below the standard 0.5 µg/kg permitted by European Union, Codex Alimentarius Commission and National Agency for Food and Drug Administration and Control (NAFDAC), in Nigeria, the AFBI levels were generally above the permissible limits of these regulatory agencies (4 - 5 µg/kg) for most foods